David Lane, Global Neoliberal Capitalism and the Alternatives: From Social Democracy to State Capitalisms - Jiang, George Hong (International Sociology, 2024)
Socialism is now gazing at us from all the windows of modern capitalism', wrote Lenin in 1917. Apparently, we are not facing a Bolshevik revolution, but people cannot help but think about how to remedy the dysfunctional capitalist system, as the practice of neoliberalism has resulted in widely recognized economic and social crises, such as recurring financial crises and increasing inequality. Critics of neoliberalism are suggesting to graft some mechanisms of socialist planning onto the market economy, while the proponents, notably some economists of the Austrian School to which Friedrich Hayek und Ludwig von Mises belonged, embrace stubbornly the idea that business cycles are in nature caused by the misbehaving government. How should people find a way out? David Lane in Cambridge believes that it is promising for industrialized countries in the West to combine certain components, respectively, of socialism and capitalism together, in order to create a more hopeful alternative to neoliberal capitalism, that is, regulated market socialism.
Keywords: Market Socialism; Neoliberal Capitalism; Varieties of Capitalism; Globalization